2011
DOI: 10.1007/s00221-011-2535-0
|View full text |Cite
|
Sign up to set email alerts
|

Mental transformation abilities in patients with unilateral and bilateral vestibular loss

Abstract: Vestibular information helps to establish a reliable gravitational frame of reference and contributes to the adequate perception of the location of one's own body in space. This information is likely to be required in spatial cognitive tasks. Indeed, previous studies suggest that the processing of vestibular information is involved in mental transformation tasks in healthy participants. In this study, we investigate whether patients with bilateral or unilateral vestibular loss show impaired ability to mentally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 54 publications
(58 reference statements)
8
103
0
1
Order By: Relevance
“…This is corroborated by mental imagery studies conducted on patients with vestibular deficits, who demonstrated impaired ability to mentally transform body images (Grabherr et al, 2011). These authors also demonstrated that a task involving mental transformation of one's own body or body parts becomes more difficult under 0G.…”
Section: Updating Internal Models Under Short-term 0gmentioning
confidence: 77%
“…This is corroborated by mental imagery studies conducted on patients with vestibular deficits, who demonstrated impaired ability to mentally transform body images (Grabherr et al, 2011). These authors also demonstrated that a task involving mental transformation of one's own body or body parts becomes more difficult under 0G.…”
Section: Updating Internal Models Under Short-term 0gmentioning
confidence: 77%
“…Whereas these previous studies tested visual and vestibular integration with respect to self-motion and vestibular influences on the processing of consciously perceived visual information, other studies investigated the effects of vestibular stimulation on visual attention (Figliozzi, Guariglia, Silvetti, Siegler, & Doricchi, 2005), bistable visual states (van Elk & Blanke, 2012), and mental rotation (Grabherr et al, 2011;van Elk & Blanke, 2014). Of relevance for vestibular input to visual awareness, it was shown by van Elk & Blanke that the direction of passive self-motion influences the perceived rotation direction of bistable rotating stimuli (that under stationary conditions have 50% of chance to be perceived to be rotating in either direction).…”
Section: Incongruent Faster Incongruent Fastermentioning
confidence: 99%
“…In addition vestibular stimulation (in the form of caloric stimulation or passive whole body rotations) has been shown to modulate the perception of bistable visual stimuli (Ngo, Liu, Tilley, Pettigrew, & Miller, 2007;van Elk & Blanke, 2012) and the mental rotation of visually presented bodily stimuli (van Elk & Blanke, 2014). Mental transformation of visually presented stimuli is also affected by damage to the vestibular end organs (Grabherr, Cuffel, Guyot, & Mast, 2011) as well as exposure to microgravity (Grabherr et al, 2007) Finally, visual perception is also affected by the observer's position with respect to gravity (Lobmaier & Mast, 2007;Lopez, Bachofner, Mercier, & Blanke, 2009). Collectively, these studies point toward extensive visuo-vestibular interactions for self-motion and visual perception.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is now well known that the vestibular system plays a role in spatial orientation [8]. Alterations in the concept of right and left can already be observed amongst patients with a unilateral vestibular deficit; the phenomenon is much more marked in the case of a bilateral deficit [9]. Accordingly, patients can be comforted.…”
Section: Discussionmentioning
confidence: 99%